2013
DOI: 10.1038/bjc.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia close to high-voltage power lines – the Geocap study, 2002–2007

Abstract: Background:High-voltage overhead power lines (HVOLs) are a source of extremely low-frequency magnetic fields (ELF-MFs), which are classified as possible risk factors for childhood acute leukaemia (AL). The study was carried out to test the hypothesis of an increased AL incidence in children living close to HVOL of 225–400 kV (VHV-HVOL) and 63–150 kV (HV-HVOL).Methods:The nationwide Geocap study included all the 2779 cases of childhood AL diagnosed in France over 2002–2007 and 30 000 contemporaneous population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 19 publications
1
50
3
Order By: Relevance
“…Even though it is likely that this association does exist in the French pediatric population it may be either a direct individual association or, alternatively, reflect the effect of some other unknown individual or Commune characteristics, which are related to residential sun exposure and influence the incidence of this particular group of ALL. This is not the case for the increased incidence of children leukemia that has been observed in France in the close vicinity of nuclear power plants [35] or high voltage power lines [3]. Both increased incidences are very localized spatially and cannot explain the trend association found in this study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Even though it is likely that this association does exist in the French pediatric population it may be either a direct individual association or, alternatively, reflect the effect of some other unknown individual or Commune characteristics, which are related to residential sun exposure and influence the incidence of this particular group of ALL. This is not the case for the increased incidence of children leukemia that has been observed in France in the close vicinity of nuclear power plants [35] or high voltage power lines [3]. Both increased incidences are very localized spatially and cannot explain the trend association found in this study.…”
Section: Discussioncontrasting
confidence: 71%
“…Several genetic diseases and polymorphisms [1], and non-genetic exposures (including H B E B factors. Some factors related to early immune stimulations and environmental exposures (pesticide use at home and, for AL, extremely low frequency electromagnetic fields) are also suspected [2,3]. Solar ultraviolet (UV) radiation, UVA (315 -400 nm) and UVB (280 -315 nm), exposures are ubiquitous with marked gradients within and between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Papers with similar objectives have been published in connection with a follow-up analysis of magnetic fields, for the Draper et al study data set (Swanson 2008) and for a French study that also recently reported childhood leukemia risks in relation to distance from transmission lines. (Bessou, Deschamps et al 2013; Sermage-Faure, Demoury et al 2013)…”
Section: Introductionmentioning
confidence: 99%
“…The researchers repeated the above study, but with a vertical magnetic field and deduced no effect on melatonin levels [12][13]. The same researchers found a phase delay in the nocturnal peak time of melatonin in hamsters.…”
Section: Literature Reviewmentioning
confidence: 90%